Assessment of the Effect of Photosynthetic Pigment Content on Moisture Level Indicators in Maize Plants - Sadriddin qizi, Anorboyeva Shakhzoda (American Journal of Biology and Natural Sciences, 2025)
In maize plants, the chlorophyll content in aboveground organs is directly proportional to yield formation. Based on this relationship, varieties with high potential capacity, as well as those characterized by elevated chlorophyll content, can be recommended for cultivation in regions with diverse climatic and soil conditions. Under the influence of unfavorable environmental factors—such as water deficit, salinity, and high air temperatures—the amount and ratio of chlorophyll pigments in plant leaves change, which in turn affects their functional activity. This article presents the results of studies on the effect of moisture availability on the photosynthetic activity of selected maize varieties.